Integration of Lending and Underwriting: Implications of Scope Economies - Kanatas, George; Qi, Jianping (Journal of Finance, 2003)
Abstract Informational scope economies provide a cost advantage to universal banks offering “one‐stop shopping” for lending and underwriting that enables them to “lock in” their clients' subsequent business. This market power reduces universal banks' incentive, relative to that of specialized investment banks, to apply costly underwriting efforts; consequently, universal banks are less successful in selling their clients' securities. Our results suggest that an integrated financial services market is less innovative than one with specialized intermediaries. Our analysis also identifies economy, intermediary, and firm characteristics that motivate either the integration or segmentation of bank lending and underwriting.